2015
DOI: 10.1002/adma.201502424
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Lead‐Free Piezoceramics with High Curie Temperatures

Abstract: A bismuth ferrite and barium titanate solid solution compound can achieve good piezoelectric properties with a high Curie temperature when fabricated with low-temperature sintering followed by a water-quenching process, with no complicated grain alignment processes performed. By adding the super-tetragonal bismuth gallium oxide to the compound, the piezoelectric properties are as good as those of lead zirconate titanate ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
217
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(233 citation statements)
references
References 51 publications
6
217
0
1
Order By: Relevance
“…BaTiO 3 ‐BiFeO 3 (BT‐BF) based ceramics have been reported to have high piezoelectric coefficient d 33 = 402 pC/N and high T C = 454°C after quenching . However, there are real challenges in convincing industry that quenched BT‐BF ceramics and multilayers are mechanically reliable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BaTiO 3 ‐BiFeO 3 (BT‐BF) based ceramics have been reported to have high piezoelectric coefficient d 33 = 402 pC/N and high T C = 454°C after quenching . However, there are real challenges in convincing industry that quenched BT‐BF ceramics and multilayers are mechanically reliable.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as Yao et al reported, Mn increases the resistivity and decreases the dielectric loss of 0.8BF‐0.2BT ceramics. However, the most successful dopants are stoichiometric or self‐compensated (e.g., Cr, Co, Al, Ga, Mg 1/2 Ti 1/2 , Zn 1/2 Ti 1/2 , and Ni 1/2 Ti 1/2 ) which improve not only the resistivity of furnace cooled ceramics but also their piezoelectric properties . Nonetheless, the d 33 of furnace‐cooled doped BF‐BT compositions is typically much smaller (163 pC/N) than that of quenched samples …”
Section: Introductionmentioning
confidence: 99%
“…91 Based on the current level of product development, the article by Shibata et al in this issue discusses the status of product transfer into applications. 92 At the same time, new materials (e.g., based on bismuth ferrite) 29 and new physical mechanisms are being discovered. In terms of new mechanisms, the opportunities to enhance depolarization temperature by either quenching 93 or using composites 94,95 and by hardening through hard second phases 96 seem particularly noteworthy.…”
Section: Future Directionsmentioning
confidence: 99%
“…Most appealing is the promise for use of BF-BT at high temperatures, not only replacing PZT, but also considerably improving high-temperature capabilities. 29 In a study by Lee et al, 29 excellent piezoelectric properties with a Curie temperature in excess of 400°C were reported when BF-BT with the addition of either Bi 1.05 GaO 3 or Figure 1. (a) The direct piezoelectric effect provides an electric charge upon application of a mechanical stress, whereas (b) the converse piezoelectric effect describes the situation where strain develops under an applied electric field.…”
mentioning
confidence: 97%
“…Lead zirconate titanate (Pb(Zr 1‐ x Ti x )O 3 , PZT) has been the most widely used ferroelectric and piezoelectric material in applications of sensors, actuators, and transducers due to its excellent overall electrical properties. However, increasing protection awareness for environmental safety has been driving the search for lead‐free piezoelectric materials over the past decades . The perovskite structured Bi 0.5 Na 0.5 TiO 3 ‐based (BNT) materials have drawn attention to desirable characteristics such as strong ferroelectric polarization and large field induced strain .…”
Section: Introductionmentioning
confidence: 99%